Pengaruh Fraud Pentagon Terhadap Kecurangan Laporan Keuangan Dengan Ukuran Perusahaan Sebagai Pemoderasi - Khusnul Khuluqi; Napisah (Universitas Warmadewa, 2022)
This study aims to examine the impact of monetary targets, incapable checking, justification, competence, what's more, self-importance on budget report extortion with firm size as directing. The populace utilized in this study is producing organizations in the shopper products area recorded on the Indonesia Stock Exchange in the 2015-2019 period. The information in this exploration were gathered by purposive testing technique, so that a total sample obtained was 22 companies and 110 financial statement data were determined as observations. The aftereffects of this study show that defense influences fiscal summary extortion while monetary objective, monetary objective, capability, and haughtiness meaningfully affect budget report misrepresentation. The rationalization variable has an impact on budget report misrepresentation with the directing variable of company size, while the financial target, financial target, competence, and arrogance have no effect on financial statement fraud with the company size moderating variable.